Diskriminasi Gender Dalam Pendidikan - Wuri Handayani (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2018)
This article is an analysis of gender discrimination discourse in education. Using qualitative methods, the literature study aims to produce substantive theoritical formations based on concept in gender discourse in education. This paper explore about the issue of gender in the educational process discrimination theoretically. The issues reviewed was what, how and what is the impact of gender discrimination in education. This study made the literature regarding themes related, formal documents on gender mainstreaming as well as qualitative data and secondary data about the gender discourse. This study uses a micro approach that is “region” process or social interactions among individuals in the process of learning, namely students and teachers, by without prejudice to the importance of the meaning of the macro approach. The results of this literature review is gender discrimination in education particularly in the learning process as a “hidden curriculum”. Gender discrimination in education occur due to the socialization process (internalization, externalization and objektivation) values of gender in the learning process so as to strengthen the gender-role identity of students and can have an impact on the achievement of education is not optimal (shortchanged).